Influence of Austenite Phase Transformation on Existing Microstructure of Low C-Mn Steel - Abro, S. H.; Chandio, A.; Jamali, A. R.; Shah, S. A. (Engineering, Technology & Applied Science Research, 2018)
Cold heading quality CHQ steel is widely used for making small components due to its excellent cold heading response. Austenite nucleation and growth morphology of a commercial CHQ steel has been studied by continuous heating experiments using lead-bath up-quenching at different heating temperatures. Modern optical microscope Olympus GX51, scanning electron microscopy techniques have been deployed to reveal and interpret the microstructure. It was found that at 740°C the microstructure shows lack of homogeneity, hence the cold-head-ability of CHQ steel is anisotropic. At high temperatures, in austenite domain, at 60sec, the resultant austenite is highly homogenous. Then the cold-head-ability properties of CHQ steel turned to be isotropic.